2012
DOI: 10.1021/jf301241n
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to the Off-Target Transport of Pyrethroid Insecticides from Urban Surfaces

Abstract: Pyrethroid insecticides used in an urban and suburban context have been found in urban creek sediments and associated with toxicity in aquatic bioassays. The objectives of this study were to evaluate the main factors contributing to the off-target transport of pyrethroid insecticides from surfaces typical of residential landscapes. Controlled rainfall simulations over concrete, bare soil, and turf plots treated individually with pyrethroid insecticides in a suspension concentrate, an emulsifiable concentrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In a more recent study by Jorgensen et al , washoff as percentage of applied mass for EC formulations from concrete surfaces were similar to the results presented in the present study (1.2–2.4% washoff), although different active ingredients and a smaller slope (4 degrees) were used. However, the suspension concentrate formulation showed much greater losses, indicating again that formulation is an important factor in washoff results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a more recent study by Jorgensen et al , washoff as percentage of applied mass for EC formulations from concrete surfaces were similar to the results presented in the present study (1.2–2.4% washoff), although different active ingredients and a smaller slope (4 degrees) were used. However, the suspension concentrate formulation showed much greater losses, indicating again that formulation is an important factor in washoff results.…”
Section: Discussionsupporting
confidence: 90%
“…Although the source was thought to be primarily professional pest controllers, they concluded that use by homeowners may also contribute. Jorgenson and Young and Jorgenson et al examined washoff from concrete surfaces and concluded that washoff is a function of the product formulation. A study by Jiang et al examined the effects of time on desorption following application of 4 pyrethroids to small concrete blocks in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrethroid washoff functions were obtained from previously published small‐scale rainfall simulation experiments . In these experiments, commercially available pyrethroid products were applied at label‐specified rates to 0.64 m 2 concrete, turf, and bare soil test plots.…”
Section: Methodsmentioning
confidence: 99%
“…Pyrethroid use in urban settings affects the ultimate fate and environmental relevance of pyrethroids in receiving surface waters. Important contributing factors include application surface type and product formulation . In the present study, we develop a simple screening‐level model that incorporates these contributing factors, empirically derived washoff functions, and observed watershed conditions for the lower American River (California, USA) for a use and exposure period of 1995 through 2010.…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of the work on pyrethroids in California has been to develop ways to minimize pyrethroid concentrations in runoff that is transported from houses via street drains into urban streams without impacting insect control. Studies examining washoff from concrete surfaces in small‐scale experiments have concluded that washoff is a function of the product formulation. Another study , examining the effects of time on desorption following application of 4 pyrethroids to small concrete blocks, also concluded that the formulation may be a factor in washoff potential.…”
Section: Introductionmentioning
confidence: 99%